Location Quotient Analysis Tourism Support Sector in Lampung - Nasrullah, Ade; Ratih, Arivina; Putri, Resha Moniyana (LPPPIPublishing, 2024)
This research was conducted to determine, analyze the tourism support sector in districts or cities, and to determine the identification and supporters of the superior tourism support in Lampung Province. Through the location quotient analysis approach in supporting the tourism sector in Lampung province. The data used is the PDRB ADHK data according to a business pitch published by BPS- Statistics Lampung Province as a reference for the Location Quotient analysis. The research Scope of the study includes 15 Regency/cities in Lampung provinces with a research period of 2019-2023. The results show that Bandar Lampung as a city of which has enormous potential in supporting and the superior tourism sectors in Lampung province. In addition, the tourism support sector was identified by the LQ value-based sector was the transportation sector of 1,272: the accommodation and food service activities sector amounted to 3.907, as well as other services activities of 1.835 in 2019-2023 years.